Mediator effects of cognitive load on the relationship between task complexity and guideline adherence among clinical nurses: a cross-sectional survey of nurses in China. - Zhang, Shan; Liu, Lu; Ding, Shu; Peng, Tingting; Wang, Jun; Wu, Ying (Journal of Research in Nursing, 2025)
Background: Suboptimal adherence to guidelines is a common phenomenon in clinical settings. Studies regarding the complexity of tasks, cognitive load, and adherence to guidelines among clinical nurses are noteworthy, but limited. Purpose: To investigate whether cognitive load mediates the association between task complexity and guideline adherence in clinical nurses. Methods: In total, 580 clinical nurses from 8 tertiary hospitals were included in the cross-sectional survey. A self-reported survey included guideline adherence, task complexity, and cognitive load. We conducted correlation and multiple linear regression analysis and performed a mediation effect analysis using PROCESS with 5000 resamples. Results: The linear regression showed that task complexity significantly predicted intrinsic cognitive load (a1 = 0.322, p < 0.001), intrinsic cognitive load significantly predicted guideline adherence (b1 = −0.113, p < 0.001), and task complexity had a direct impact on guideline adherence (c ′ = 0.126, p < 0.001). Both intrinsic cognitive load (effect size = −0.037, 95%CI: −0.061, −0.019) and germane cognitive load (effect size = 0.180, 95%CI: −0.269, −0.171) played a partial mediating effect between task complexity and guideline adherence among nurses, contributing to 53.16% of the overall effect. Conclusions/Implications for practice: Nursing administrators should prioritise the cognitive load for clinical nurses when allocating intricate assignments.